(3OjhGf GHf GdQhejs - (3Ydj Hf GdYHGS Hf LQjL, Ch LhQLjS, GdQhej, CHh GdMSf,J (B283 (3g` s ((3YHOGdQMef Hf CMeO Hf YHGS CMeO s)
(3ChdgG (B:s
(3bGd Ydj Hf GdYHGS Hf LQjL GdQhej jLhG CHG jhSa GdObGb(B: (3CSCdJ Mjf hbaJ Ce de JSCd OefG YaJ acCfgG de JMdd s
(3BNQgG (B:s
(3dgaj YdjgG hCfG GdRYje deYOI TjWGfgG QLje s
(3JedcgG GdCOjH Ndjd Hf CjHc GdUaOj SfI (B764(3g`s
(3hYdjgG JedjcGJ CNQi cJHJ HQSe NRGfI GdCejQ TgGH GdOjf CMeO Hf YeGO GdOjf OGhO Hf YRGdOjf ehScs
(3fSNI KGfjI GdbSe GdKGfjs
(3hQOJ GjVG JMJ Qbe (B2191 s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
Keywords: (3GdCOHs